2004
DOI: 10.1023/b:boli.0000045756.54006.17
|View full text |Cite
|
Sign up to set email alerts
|

Sustained therapeutic effects of oral miglustat (Zavesca, N‐butyldeoxynojirimycin, OGT 918) in type I Gaucher disease

Abstract: It has been shown that treatment with miglustat (Zavesca, N-butyldeoxynojirimycin, OGT 918) improves key clinical features of type I Gaucher disease after 1 year of treatment. This study reports longer-term efficacy and safety data. Patients who had completed 12 months of treatment with open-label miglustat (100-300 mg three times daily) were enrolled to continue with therapy in an extension study. Data are presented up to month 36. Liver and spleen volumes measured by CT or MRI were scheduled every 6 months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
154
0
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(163 citation statements)
references
References 13 publications
4
154
0
5
Order By: Relevance
“…Since it slows down the production of glycosphingolipids, it should be effective in reducing storage of these compounds. Although positive effects of such treatment in clinical trials were reported (Elstein et al 2004;Pastores et al 2005), its efficacy in Gaucher disease has recently been questioned (Tylki-Szymanska et al 2011;Machaczka et al 2012).…”
Section: Substrate Reduction Therapies (Srps) For Mpsmentioning
confidence: 99%
“…Since it slows down the production of glycosphingolipids, it should be effective in reducing storage of these compounds. Although positive effects of such treatment in clinical trials were reported (Elstein et al 2004;Pastores et al 2005), its efficacy in Gaucher disease has recently been questioned (Tylki-Szymanska et al 2011;Machaczka et al 2012).…”
Section: Substrate Reduction Therapies (Srps) For Mpsmentioning
confidence: 99%
“…While effective in managing the visceral symptoms of the disease, enzyme replacement therapy is expensive and cannot address the neurological defects because the replacement enzyme is unable to cross the blood-brain barrier [4]. Treatment with the iminosugar N-butyldeoxynojirimycin (NB-DNJ, Miglustat), an inhibitor of glucosylceramide synthase, has been shown to improve liver and spleen volume and hematological parameters in type 1 Gaucher patients [5]. However, the administration of NB-DNJ is observed to cause several significant side effects including peripheral neuropathy and gastrointestinal complications [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment for individuals with GCase deficiencies involves either enzyme replacement therapy with imiglucerase (Cerezyme, Genzyme Corp.) [3] or less frequently, substrate reduction therapy with mi-glustat (Zavesca, Actelion Ltd.). [4,5] Recently a third therapeutic approach, enzyme enhancement therapy (EET), utilizing small molecule pharmacological chaperone (PC) has been proposed. Currently, isofagomine (IFG), an iminosugar and potent competitive inhibitor of GCase (Plicera, Amicus Therapeutics Inc.) is being evaluated clinically as a PC for EET.…”
mentioning
confidence: 99%